Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1111/j.1747-7379.2007.00115.x
|View full text |Cite
|
Sign up to set email alerts
|

Immigrants' TANF Eligibility, 1996–2003: What Explains the New Across-State Inequalities?

Abstract: Why did some states adopt stringent TANF‐eligibility policies toward immigrants, while others implemented more lenient rules throughout the post‐1996 welfare reform period? We use immigrant‐specific welfare rule measures to examine predominant theoretical frameworks for understanding state stringency in welfare policy. Analysis, utilizing a simultaneous equations modeling (SEM) strategy, uses annual data for all states. Results show consistent support for the median voter (primarily, the percent of liberal vot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 36 publications
3
28
1
Order By: Relevance
“…Some states attach citizenship requirements to welfare boundaries, statutorily denying immigrants access to public assistance (Filindra ; Fix, Capps, and Kaushal 2009; Graefe et al . ; Hero and Preuhs ; Monogan ; Tichenor ).…”
Section: Immigrant Welfare Boundaries In An Age Of Devolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some states attach citizenship requirements to welfare boundaries, statutorily denying immigrants access to public assistance (Filindra ; Fix, Capps, and Kaushal 2009; Graefe et al . ; Hero and Preuhs ; Monogan ; Tichenor ).…”
Section: Immigrant Welfare Boundaries In An Age Of Devolutionmentioning
confidence: 99%
“…Third, the economic situation of the state can increase the demand for generous social programs among the public and influence the generosity of the legislature to fund social spending programs by providing a means to increase funding (Graefe et al . ; Plotnick and Winters 1985; Tweedie 1994). We control for the state's unemployment rate and gross domestic product (GDP) per capita.…”
Section: Variables For the State‐level Analysismentioning
confidence: 99%
“…The evidence from these other studies has been, however, quite mixed (see Blank, 2002 for a review of these studies). Notably, although Hispanic women -many of whom were immigrants, had the highest rates of teenaged and non-marital childbearing of any major racial or ethnic group in the United States before welfare reform (Graefe et al, 2008), 3 none of the studies examined how immigrant fertility was impacted by PRWORA and the state provisions. In fact, we only know of one study examining the fertility of Hispanic immigrants (i.e.…”
Section: Background On Welfare Reform and Immigrant Fertilitymentioning
confidence: 99%
“…Early work on this question indicated that the size of the state's noncitizen population was unrelated to program generosity toward immigrants in the first years following PRWORA (Zimmerman and Tumlin, 1999). However, states with strong immigrant advocacy groups and a liberal voting public were more consistent predictors of state generosity towards immigrants (Graefe et al 2008). Kalil and Ziol-Guest (2009) use SIPP data to examine, instead, the effect of PRWORA on the health of the children of immigrants.…”
Section: Background On Welfare Reform and Immigrant Fertilitymentioning
confidence: 99%
See 1 more Smart Citation